2003
DOI: 10.1046/j.1341-8076.2003.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sensitivity and specificity of breast tumor diagnosis by primary health care providers (Behvarz) using clinical examination by obstetrician as a gold standard

Abstract: Based on these findings, the sensitivity and specificity of diagnosis of breast tumors made by Behvarzes was 95.8% and 99.56%, respectively, compared with those made by specialists. Considering the obtained results, the screening program for breast tumors by Behvarzes can be very helpful in early diagnosis of breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to the National Death Survey, the recorded mortality rate was 2.7 per 100,000 women population, and the burden in disability adjusted life years was 16,792 years in 2003 (5,6). There are many reports about locally advanced breast cancer in Iran (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: To the Editormentioning
confidence: 99%
“…According to the National Death Survey, the recorded mortality rate was 2.7 per 100,000 women population, and the burden in disability adjusted life years was 16,792 years in 2003 (5,6). There are many reports about locally advanced breast cancer in Iran (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: To the Editormentioning
confidence: 99%
“…In order to evaluate convergent and divergent validity of the WSID‐SF and DLSA, women were asked to complete the paper‐and‐pencil versions of selected patient‐reported questionnaires including FSFI, MSIQ, FSDS, Dyadic Adjustment Scale (DAS) [20], and the Kellner Symptom Questionnaire (KSQ) [21]. These questionnaires were administered at both Visit 1 and Visit 2.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported the involvement of multiple stakeholders, including ministry of health officials, breast cancer survivors, nurses and oncologists, 33 36 47 whereas others were led by one stakeholder, such as a nurse. 45 Trainings ranged from information dissemination models such as lectures 46 to interactive workshops with practical demonstrations using model breasts, 41 role-play exercises and case discussions. 36 The heterogeneity across these categories is perhaps reflective of the variability of locally available resources.…”
Section: How Are Chws Trained and Assessed For Early Detection Of Brementioning
confidence: 99%